2016
DOI: 10.1007/s11130-016-0539-4
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Bioactive Properties of Muffins Enriched with Raspberry and Cranberry Pomace Powder: A Promising Application of Fruit By-Products Rich in Biocompounds

Abstract: The objective of this study was to determine the effects on quality of incorporating raspberry and cranberry pomaces into American-style muffins prepared under various baking conditions. The different baking conditions did not affect the texture or microstructure of the control muffins. The enhanced samples baked at 140 °C for 30 min were characterized by a harder texture than the control muffins and by a distributed protein matrix and distorted starch granules, while those baked at 240 °C for 15 min had a moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 25 publications
0
63
0
2
Order By: Relevance
“…Mildner‐Szkudlarz et al . () reported that harder texture of fibre‐enriched muffins might be attributed to the dilution of gluten, and higher water absorption upon addition of the fibre fraction. Chewiness is the amount of energy and time needed to masticate a food for swallowing.…”
Section: Resultsmentioning
confidence: 97%
“…Mildner‐Szkudlarz et al . () reported that harder texture of fibre‐enriched muffins might be attributed to the dilution of gluten, and higher water absorption upon addition of the fibre fraction. Chewiness is the amount of energy and time needed to masticate a food for swallowing.…”
Section: Resultsmentioning
confidence: 97%
“…Cranberry fruit is a transformational functional food and a nutraceutical due to the presence of various biologically active substances (Howell et al, 1998). The use of cranberries in foods is very common in Canada and in the United States as a common ingredient in baking goods (muffins, scones, cakes and breads), soups and stews (Mildner-Szkudlarz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These kind of products could be a great carrier of substances increasing the nutritional value of a product. Other authors proposed to increase the nutritional value of sponge cakes with fruit pomaces as a source of polyphenols Mildner-Szkudlarz et al, 2016). The high quality of baked food is of great importance, since these products are often used and stored at room temperature for a certain time before consumption (Al-Bandak and Oreopoulou, 2011).…”
Section: Introductionmentioning
confidence: 99%